Respuesta :

[tex]\huge\text{Hey there!}[/tex]

[tex]\textsf{Assuming:}[/tex]

[tex]\mathsf{w + (w - \dfrac{12}{2^2} \times 3)(7)}[/tex]

[tex]\textsf{If so:}[/tex]

[tex]\mathsf{w + (w - \dfrac{12}{2^2} \times 3)(7)}[/tex]

[tex]\mathsf{= 10 + (10 - \dfrac{12}{2^2} \times 3)(7)}[/tex]

[tex]\mathsf{= 10 + (10 - \dfrac{12}{2\times2} \times 3)(7)}[/tex]

[tex]\mathsf{= 10 + (10 - \dfrac{12}{4} \times 3)(7)}[/tex]

[tex]\mathsf{= 10 + (10 -3 \times 3)(7)}[/tex]

[tex]\mathsf{= 10 + (10 - 9)(7)}[/tex]

[tex]\mathsf{= 10 + (1)(7)}[/tex]

[tex]\mathsf{= 10 + 7}[/tex]

[tex]\mathsf{= 17}[/tex]

[tex]\huge\textsf{Therefore, your answer should be:}[/tex]

[tex]\huge\boxed{\textbf{Option D. }\frak{017}}\huge\checkmark[/tex]

[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]